Article RETRACTED due to manipulation by the authors and citations Implementing management of the physical fitness education program for the drug rehabilitation patients in drug addict therapy centre - Deny Setiawan Wayoi; Hendra Setyawan; Suyanto Suyanto; Yudik Prasetyo; Sadewo Tri Lastiono; Nurkadri Nurkadri; Baskoro Nugroho Putro; Harmanto Harmanto; Arief Darmawan; Gusliana HB; Özgür Eken (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. This research analyses the urgency of Implementation of Physical Fitness Education Program Management for Drug Rehabilitation Patients at the Bidayatussalikin Islamic Boarding School (BIBS) Drug Addict Therapy House in Indonesia. This research was a mixed-method research. The quantitative sample consisted of 65 BIBS drug rehabilitation students. The qualitative sample included 6 expert informants. The conclusion is the implementation of physical fitness education programme management as a means of accelerating non-medical rehabilitation for students as former drug addicts needs to be implemented. This programme can be used as a means of accelerating the non-medical healing process through; strengthening physical fitness components, repairing the body's nerve cells, encouraging the release of the hormones dopamine and endorphins that trigger happiness, reducing stress, managing emotions, stabilising mood, channeling positive energy, avoiding empty thoughts, helping restore damaged memory, and entertaining the students as former drug addicts. The conclusion of this study emphasizes the importance of implementing a structured physical fitness education pro-gram in drug rehabilitation centers. The findings confirm that such programs not only provide significant physical health benefits, but also support psychological recovery and encourage positive routines for patients. Physical fitness programs, integrated in drug rehabilitation strategies, should be considered a crucial and indispensable component, due to their contribution to physical and mental well-being during the recovery process. Research has also shown the integral role of rehabilitation in helping individuals suffering from substance use disorders to achieve recovery and pre-vent relapse. By incorporating approaches that cover physical, psychological, social, and spiritual aspects, rehabilitation programs can effectively support the holistic well-being and successful recovery of individuals undergoing rehabili-tation from substance dependence.